2021
DOI: 10.1186/s13098-021-00760-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum free triiodothyronine is inversely associated with diabetic peripheral neuropathy but not with carotid atherosclerotic lesions in euthyroid patients with type 2 diabetes

Abstract: Background The associations between serum free triiodothyronine (FT3) and diabetic peripheral neuropatprohy (DPN)/carotid atherosclerotic lesions in euthyroid patients with type 2 diabetes are still unclear. The purpose of our study was to explore the relations of FT3 to DPN and carotid atherosclerotic lesions in Chinese type 2 diabetes inpatients with euthyroid function. Methods 2477 euthyroid inpatients with type 2 diabetes were recruited and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Previous studies have shown that fT3 level was negatively associated with risk of abnormal nerve conduction (56). Meanwhile, Li et al demonstrated a negative association of fT3 with DPN in T2DM patients with normal thyroid function (57). This is consistent with our findings.…”
Section: B Asupporting
confidence: 93%
“…Previous studies have shown that fT3 level was negatively associated with risk of abnormal nerve conduction (56). Meanwhile, Li et al demonstrated a negative association of fT3 with DPN in T2DM patients with normal thyroid function (57). This is consistent with our findings.…”
Section: B Asupporting
confidence: 93%
“…Cross-sectional studies showed that subclinical hypothyroidism was highly prevalent in patients with DR and DPN, and was closely related to their severity. [44][45][46] Low FT3 within the normal range was also indicated to be independently associated with DR 10 and DPN 47 in euthyroid patients with T2DM in recently researches. But notably, the relationships between thyroid hormone levels and diabetic microvascular complications such as DR were found to be weak or negative in some researches 48 and there is a lack of large-scale prospective clinical research on the impact of thyroid on the occurrence and course of diabetic chronic complications.…”
mentioning
confidence: 91%
“…Thyroid dysfunction and diabetes mellitus are closely linked [10] , while normal thyroid hormone is also associated with macrovascular and microvascular complications in type 2 diabetes [11][12][13][14][15] , but the speci c mechanisms are still unclear. We speculated that the uctuations of thyroid hormones in uenced glycemic variability, and the increased glycemic variability contributed to various complications.…”
Section: Introductionmentioning
confidence: 99%